Analisis Kemampuan Berpikir Tingkat Tinggi Siswa pada Materi Keanekaragaman Hayati di Kelas X - Stivani, Elly; Djulia, Ely; Hasairin, Ashar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the students' higher order thinking skills on biodiversity material in class X. This research uses a quantitative descriptive approach. The sample of this study was class X students consisting of 104 people determined by cluster random sampling technique. The instrument used was a test question in the form of an essay of 12 items on biodiversity material. The results showed that students' higher order thinking skills on biodiversity material in class X were at very low criteria with the acquisition of an average student score of 44.5%. In each indicator, it was found that the C4 indicator of class X students was very low with a percentage of 44.3%, the C5 indicator was very low with a percentage of 40.0%, and the C6 indicator was very low with a percentage of 46.0%. Thus, it can be concluded that to be able to improve the higher order thinking skills of grade X students, students begin to familiarize themselves with reading various literatures, solve HOTS-based problems, and students must use various learning strategies.